2006
DOI: 10.1002/adsc.200505373
|View full text |Cite
|
Sign up to set email alerts
|

Small Peptide‐Catalyzed Enantioselective Addition of Ketones to Nitroolefins

Abstract: Abstract:The direct small peptide-catalyzed enantioselective Michael addition of ketones to nitroolefins is presented. Simple di-and tripeptides derived from alanine catalyze the asymmetric Michael additions with high stereoselectivity and furnish the corresponding Michael products in high yield with up to 68 : 1 dr and 98% ee. The study demonstrates that small, readily prepared peptides with increased structural complexity as compared to the parent amino acid mediate the asymmetric Michael reaction with super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…12 Wang et al described a chiral pyrrolidine sulfonamide catalyst, with which, they realized the Michael conjugate additions of aldehydes to nitrostyrenes with high levels of enantioselectivity (89-99% ee) and diastereoselectivity (20:1 dr). 13 Very recently, some simple diamines and triamines, 14 functionalized chiral ionic liquids, 15 and small peptids 16 were reported as efficient catalysts for the addition of cyclic ketones and some aldehydes to nitroolefins.…”
Section: Introductionmentioning
confidence: 99%
“…12 Wang et al described a chiral pyrrolidine sulfonamide catalyst, with which, they realized the Michael conjugate additions of aldehydes to nitrostyrenes with high levels of enantioselectivity (89-99% ee) and diastereoselectivity (20:1 dr). 13 Very recently, some simple diamines and triamines, 14 functionalized chiral ionic liquids, 15 and small peptids 16 were reported as efficient catalysts for the addition of cyclic ketones and some aldehydes to nitroolefins.…”
Section: Introductionmentioning
confidence: 99%
“…A related study by Enders showed a strong solvent effect in the reaction since in MeOH the enantioselectivity could be increased to 76% for the major syn diastereomer in the reaction between 3-pentanone and trans-β-nitrostyrene employing a 20 mol% of Lproline as catalyst. [7] Since these preliminary studies, very effective catalytic systems (2-20) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] have been developed for the asymmetric Michael reaction of ketones with nitroalkenes being the process generally syn-selective (Scheme 1). Best improvements to this reaction have been mostly achieved using pyrrolidine-based catalytic derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, catalyst 15 and the fluorous sulfonamide 19 can be easily recycled by precipitation and fluorous solid-phase extraction, respectively, and reused without significant loss of activity and stereoselectivity. [7] up to 76% ee 2 [8] up to 81% ee 3 [9] up to 99% ee [18] up to 86% ee 13 [19] up to 91% ee up to 91% ee 5 [11] up to 68% ee 6 [12] up to 92% ee 7 [13] up to 94% ee 8 [14] up to 87% ee 9 [15] up to 98% ee 10 [16] up to 98% ee 11 [17] up to 91% ee 14 [20] up to 98% ee 15 [21] up to 99% ee 16 [22] up to 90% ee 17 [23] up to 99% ee 18 [24] up to 99% ee 20 [26] up to 97% ee 19 [25] up to 95% ee …”
Section: Introductionmentioning
confidence: 99%
“…[1] In the research field of organocatalysis, [2,3] there are several elegant reports on the amine-catalyzed asymmetric addition of ketones and aldehydes to nitrostyrenes. [4][5][6] Moreover, well-designed catalytic enantioselective conjugate additions of aldehydes to vinyl sulfones, [7] maleimides, [8] benzoquinones, [9] enones [10] and vinyl phosphonates [11] have recently been reported. However, only the amine-catalyzed conjugate addition of ketones to alkylidinemalonates is known.…”
mentioning
confidence: 99%